Modeling space-resolved ion dynamics in ECR plasmas for predicting in-plasma β-decay rates - Mishra, Bharat; Galatà , Alessio; Pidatella , Angelo; Biri , Sándor; Mauro , Giorgio Sebastiano; Naselli , Eugenia; Rácz , Richárd; Torrisi , Giuseppe; Mascali , David (Frontiers in Physics, 2022)
Lifetimes of radioactive nuclei are known to be affected by the level configurations of their respective atomic shells. Immersing such isotopes in environments composed of energetic charged particles like stellar plasmas can result in β-decay rates orders of magnitude different from those measured terrestrially. Accurate knowledge of the relation between plasma parameters and nuclear decay rates are essential for reducing uncertainties in present nucleosynthesis models, and this is precisely the aim of the PANDORA experiment. Currently experimental evidence is available for fully stripped ions in storage rings alone, but the full effect of a charge state distribution (CSD) as exists in plasmas is only modelled theoretically. PANDORA aims to be the first to verify these models by measuring the β-decay rates of select isotopes embedded in electron cyclotron resonance (ECR) plasmas. To do so, it is necessary to consider the spatial inhomogeneity and anisotropy of plasma ion properties as well as the Non-Local Thermodynamic Equilibrium (NLTE) nature of the system. We present here a 3D ion dynamics model combining a quasi-stationary particle-in-cell (PIC) code to track the motion of macroparticles in a pre-simulated electron cloud while simultaneously employing a Monte Carlo (MC) routine to check for relevant reactions describing the ion population kinetics. The simulation scheme is robust, comprehensive, makes few assumptions about the state of the plasma and can be extended to include more detailed physics. We describe the first results on the 3D variation of CSD of ions both confined and lost from the ECR trap, as obtained from the application of the method to light nuclei. The work culminates in some perspectives and outlook on code optimization, with a potential to be a powerful tool not only in the application of ECR plasmas but for fundamental studies of the device itself.